Victorian renovations of the novel : narrative annexes and the boundries of representation - Keen, Suzanne (Cambridge studies in nineteenth-century literature and culture ;, 1998)
This study of narrative technique in Victorian novels introduces the concept of 'narrative annexes' whereby unexpected characters, impermissible subjects and plot-changing events are introduced within fictional worlds which otherwise exclude them. They are marked by the crossing of borders into previously unrepresented places and new genres or modes, challenging Victorian cultural and literary norms. Suzanne Keen's original readings of novels by Charlotte Brontë, Dickens, Disraeli, Hardy, Kingsley, Trollope, and Wells show these writers negotiating the boundaries of representation to reveal in narrative annexes the subjects (notably sexuality and social class) which contemporary critics sought to exclude from the realm of the novel. Fears of disease, of working men, of Popery, of dark-skinned 'others', of the poor who toil and starve in close proximity to the rectories, homes, clubs and walled gardens of Victorian polite society draw readers down narrow alleys, through thorny hedges, across desolate heaths, into narrative annexes.